2022
DOI: 10.1126/scitranslmed.abm8646
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary microbiome and gene expression signatures differentiate lung function in pediatric hematopoietic cell transplant candidates

Abstract: Impaired baseline lung function is associated with mortality after pediatric allogeneic hematopoietic cell transplantation (HCT), yet limited knowledge of the molecular pathways that characterize pretransplant lung function has hindered the development of lung-targeted interventions. In this study, we quantified the association between bronchoalveolar lavage (BAL) metatranscriptomes and paired pulmonary function tests performed a median of 1 to 2 weeks before allogeneic HCT in 104 children in The Netherlands. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Staphylococcus spp.) had higher post-HSCT mortality compared to those children with diverse oropharyngeal microbiomes and lacking inflammation [23]. This dysbiosis was shown to be associated with pre-HSCT reduction in lung function (reduced forced vital capacity <60% predicted) and post-HSCT lung injury, specifically reduced airway epithelial cell integrity.…”
Section: Pulmonary Microbiomementioning
confidence: 93%
See 2 more Smart Citations
“…Staphylococcus spp.) had higher post-HSCT mortality compared to those children with diverse oropharyngeal microbiomes and lacking inflammation [23]. This dysbiosis was shown to be associated with pre-HSCT reduction in lung function (reduced forced vital capacity <60% predicted) and post-HSCT lung injury, specifically reduced airway epithelial cell integrity.…”
Section: Pulmonary Microbiomementioning
confidence: 93%
“…This dysbiosis was shown to be associated with pre-HSCT reduction in lung function (reduced forced vital capacity <60% predicted) and post-HSCT lung injury, specifically reduced airway epithelial cell integrity. The hypothesis that microbiome depletion in combination with alveolar injury during HSCT due to chemotherapy, radiation or infection, promotes a pro-fibrotic response [23]. Post-HSCT pulmonary fibrosis is exceedingly difficult to treat and is often fatal.…”
Section: Novel Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the skin microbiome 30,31 found that cutaneous aGVHD was associated with increased abundances of Staphylococcus , a finding highly reminiscent of that seen in children with atopic dermatitis 32 . Pulmonary toxicities and changes in the pulmonary microbiome have also been found to be coassociated in pediatric alloHCT patients 33,34 . Changes in the ocular microbiota have also been observed in patients with ocular cGVHD, including in composition of bacteria as well as viruses 35 .…”
Section: The Microbiome and Allohctmentioning
confidence: 98%
“…32 Pulmonary toxicities and changes in the pulmonary microbiome have also been found to be coassociated in pediatric alloHCT patients. 33,34 Changes in the ocular microbiota have also been observed in patients with ocular cGVHD, including in composition of bacteria as well as viruses. 35 Whether the microbiome of the oral cavity or upper gut could be similarly associated with upper GI aGVHD has not yet been well studied, although the dental biofilm microbiome has been reported to be associated with aGVHD.…”
Section: Microbiome Deep Sequencing In Allohctmentioning
confidence: 99%